(untitled) (Vietnam Journal of Community Medicine, 2021)
Aim: To describe quality life’s colorectal cancer patients who are being treated at Thai Nguyen oncology center from June 2020 to August 2020. Objects and method: The descriptive cross- sectional study was conducted over 68 patients diagnosed with colorectal cancer by face to face interview using the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 and the EORTC QLQ-CR29. Results: Mean of overall health score was 51,96±18,78; mean of functional score was 21,49±12,42 (1,71–47,06). In functional sector, social function was scored lowest. In symptomatic scale, appetite loss was scored highest (47,06). Conclusion: Quality of life of colorectal cancer patients was medium level. Highest scores were observed for appetite loss and fatigue. To improve quality life’s patients, medical staffs need to keep enhancing symptoms and function for patients during treatment.